Multimedia-Based Learning Management Interactive Learning in Improving Students’ Digital Literacy - Miftahul Jannah; Yasir Arafat; Mahasir Mahasir (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aimed to describe the application, implementation, and evaluation of interactive multimedia-based learning management as a strategy to improve the digital literacy of third- and fourth-grade students at SD Negeri 22 Sembawa. Employing a descriptive qualitative method, the research involved teachers, the principal, and students as subjects. Data were analyzed through the processes of reduction, display, and conclusion drawing/verification. The strategy proved effective in enhancing students’ abilities to access, understand, evaluate, and process digital information. Teachers successfully adopted more creative, student-centered planning and evaluation. Key challenges included limited devices, constrained instructional time, and gaps in teachers’ digital competencies. The study uniquely integrates the framework of systematic learning management planning, implementation, evaluation with interactive multimedia tools, specifically targeting digital literacy development in lower primary education. The findings provide an actionable model for schools, highlighting the need for targeted teacher training and resource allocation to overcome technological and pedagogical barriers when implementing similar digital literacy programs. It contributes a validated, on-the-ground case study demonstrating how structured learning management can successfully harness interactive multimedia to build foundational digital competencies in young learners.